Vaccines targeting ESR1 activating mutations elicit anti-tumor immune responses and suppress estrogen signaling in therapy resistant ER+ breast cancer - Gabrielle P. Dailey; Christopher A. Rabiola; Gangjun Lei; Junping Wei; Xiao-Yi Yang; Tao Wang; Cong-Xiao Liu; Melissa Gajda; Amy C. Hobeika; Amanda Summers; Robert D. Marek; Michael A. Morse; et al. (Taylor & Francis Group, 2024)
ABSTRACTER+ breast cancers (BC) are characterized by the elevated expression and signaling of estrogen receptor alpha (ESR1), which renders them sensitive to anti-endocrine therapy. While these therapies are clinically effective, prolonged treatment inevitably results in therapeutic resistance, which can occur through the emergence of gain-of-function mutations in ESR1. The central importance of ESR1 and development of mutated forms of ESR1 suggest that vaccines targeting these proteins could potentially be effective in preventing or treating endocrine resistance. To explore the potential of this approach, we developed several recombinant vaccines encoding different mutant forms of ESR1 (ESR1mut) and validated their ability to elicit ESR1-specific T cell responses. We then developed novel ESR1mut-expressing murine mammary cancer models to test the anti-tumor potential of ESR1mut vaccines. We found that these vaccines could suppress tumor growth, ESR1mut expression and estrogen signaling in vivo. To illustrate the applicability of these findings, we utilize HPLC to demonstrate the presentation of ESR1 and ESR1mut peptides on human ER+ BC cell MHC complexes. We then show the presence of human T cells reactive to ESR1mut epitopes in an ER+ BC patient. These findings support the development of ESR1mut vaccines, which we are testing in a Phase I clinical trial.